FLAGRANTE INVISÍVEL E FUNDADAS RAZÕES: A busca e apreensão domiciliar e o Tema 280 do Supremo Tribunal Federal - MOURA, LAÍS LEITE (2025)
The present work aims to analyze the search and seizure procedure in a person’s residence, as disciplined by the article 240 and its following articles, present in the Criminal Procedure Code of Brazil, its requirements and legal proceedings, as well as its instances of occurrence and its confrontation against the constitutional guarantee of home inviolability. This study seeks to focus on the hypothesis of a home search without a legal judicial warrant, due to the repression of a flagrant crime, as well as to analyze the problems with the expression substantiated reasons, shedding light on its lack of assertiveness and the possibility that it’s used as a subjective justification of exploratory actions by police forces. The positions of different national High Courts were evaluated, as well as their intentions of filling the present normative gap, with a direct study of cases judged by the Federal Supreme Court and by the National High Court of Brazil, highlighting the legal insecurity associated with the subject and the need for clearer legislative markings. Lastly, the main consequences of this legal gap are analyzed, with the study of fishing expeditions and the invalidation of proof, which result in the inefficiency of the criminal prosecution. To do so, this work employs the deductive method, with a research methodology that is predominantly bibliographical and documental, with a qualitative approach. This work is made legitimate by the need to expand the interpretative exercise of the expression substantiated reasons, given its signification gap, and also to discuss the consequences of such omission, emphasizing the need for normative regulation.